International visibility of thesis and dissertations from ULisboa through the Institutional Repositories: Gateway for Open Science - Sanches, Tatiana (2022)
Institutional repositories of universities are initiatives that integrate the concept of Open Science, enhancing the free circulation of academic and scientific production. The current University of Lisbon (ULisboa) results from the fusion of the former University of Lisbon and Technical University of Lisbon, in 2013. Currently, ULisboa comprises 18 schools. Since the fusion, University of Lisbon still has two independent institutional repositories based on DSpace – the Repositório.UL and the UTL Repository. Focused on the collection of theses and dissertations, the aim of the following study is to look at the scientific production of ULisboa and analyse the international visibility between 2010 and 2019. The final goal is to demonstrate how the use of institutional repositories contributes to enhancing science dissemination, research, and researchers’ visibility and promotes access to knowledge, improving the quality of the information available on the web. The self-archive policies of the University of Lisbon express as the major goals, to gather and organize systematically the set of intellectual, academic and scientific production; to disseminate, provide access and more visibility to research developed; to improve monitoring, evaluation and management of research and teaching activities and to promote the enhancement and preservation of the intellectual and cultural heritage of this University.